Transparency in health and health care in the United States : law and ethics / edited by Holly Fernandez Lynch, I. Glenn Cohen, Carmel Shachar, Barbara J. Evans. - Lynch, Holly Fernandez; Cohen, I. Glenn; Shachar, Carmel; Evans, Barbara J. (Cambridge University Press, 2019)
Transparency is a concept that is becoming increasingly lauded as a solution to a host of problems in the American health care system. Transparency initiatives show great promise, including empowering patients and other stakeholders to make more efficient decisions, improve resource allocation, and better regulate the health care industry. Nevertheless, transparency is not a cure-all for the problems facing the modern health care system. The authors of this volume present a nuanced view of transparency, exploring ways in which transparency has succeeded and ways in which transparency initiatives have room for improvement. Working at the intersection of law, medicine, ethics, and business, the book goes beyond the buzzwords to the heart of transparency's transformative potential, while interrogating its obstacles and downsides. It should be read by anyone looking for a better understanding of transparency in the health care context.